2013
DOI: 10.4028/www.scientific.net/ssp.205-206.151
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Point Defects in Silicon: New Results after a Long-Time Debate

Abstract: The contributions of vacancies and self-interstitials to silicon (Si) self-diffusion are a matter of debate since many years. These native defects are involved in dopant diffusion and the formation of defect clusters and thus influence many processes that take place during Si single crystal growth and the fabrication of silicon based electronic devices. Considering their relevance it is remarkable that present data about the properties of native point defects in Si are still limited and controversy. This work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…The generation rate of electron−hole pairs caused by an incident monochromatic radiation of l wavelength perpen− dicular to the p−n junction plane of the photodiode as a func− tion of the distance from the junction plane (x = 0) (neglect− ing the space−charge region) is expressed by the following equation [3][4][5] …”
Section: Measurement Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The generation rate of electron−hole pairs caused by an incident monochromatic radiation of l wavelength perpen− dicular to the p−n junction plane of the photodiode as a func− tion of the distance from the junction plane (x = 0) (neglect− ing the space−charge region) is expressed by the following equation [3][4][5] …”
Section: Measurement Methodologymentioning
confidence: 99%
“…Influence of native defects generated during a manufacturing process on the recombination parameters of the material is still controver− sial as clearly highlighted in Ref. 3 and requires further investigation and verification. In this article we first show a subtle spatial distribution of minority carrier diffusion length in high resistivity (>1 kW cm) epitaxy layers condi− tioned by spatial distribution of punctual defects in vacan− cies−oxygen complex formed during epitaxial growth with the MOCVD method.…”
Section: Introductionmentioning
confidence: 99%
“…Their diffusion properties are relatively well-established compared to vacancies, since extremely precise measurements of self-diffusivities are required in the latter case. Discrepancies between estimations of vacancy contribution to self-diffusion [34,35,36] indicate that this task is very challenging from the experimental point of view, see discussion in [36] for details. Therefore, an application of MTP to this problem could be of interest.…”
Section: Calculation Of Diffusion Coefficientsmentioning
confidence: 99%
“…Bracht et al (2003) determined a value of 1.8 AE 0.5 eV from radiation enhanced self-diffusion experiments at temperatures between 780 and 872°C using 2-MeV proton irradiations for various times and proton fluxes, and Ranki and Saarinen (2004) determined a value of 1.3 AE 0.4 eV from positron-annihilation experiments of thermal vacancies generated at high temperature in highly As-and P-doped Si. In a recent review of self-diffusion studies in silicon by means of isotopically enriched silicon, Bracht et al (2014) found that the temperature dependence of self-diffusion is most consistently described with temperature-dependent vacancy formation and migration enthalpies, and they find the best description with a vacancy-migration energy varying from 0.5 eV at 700°C to 0.8 eV at 1400°C. We note that the low temperature value is not very different from the cryogenic value found by Watkins (1986).…”
Section: Diffusion Mechanismmentioning
confidence: 99%